Ubiquitous LibGuides: Variations in Presence, Production, Application, and Convention. Issue 3 (18th August 2021) - Neuhaus, Chris; Cox, Angie; Gruber, Anne Marie; Kelly, Jim; Koh, HyunSeung; Bowling, Claire; Bunz, Gail
Abstract: The LibGuides platform, a content management system (CMS) from Springshare, has become an integral part of the online presence for many academic libraries. Neither Springshare nor other recent studies have provided an in-depth look at the evolving nature of LibGuides adoption, production and application across university and college categories. This study compared the prevalence and production of LibGuides to other forms of library guides at 799 academic libraries throughout the United States. LibGuides naming conventions were recorded and compared. The use of LibGuides CMS software to create library websites was also documented. This study found that there are clear differences in LibGuides adoption and production across various types of institutions. LibGuides naming conventions were fairly consistent across all types of institutions. Institutions using LibGuides software produced substantially more library guides than institutions without this software. A small but significant portion of all non-R1 libraries in this study are now utilizing LibGuides software to create the majority of their library websites.